2009
DOI: 10.1111/j.1755-148x.2008.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on skin repigmentation therapies in vitiligo

Abstract: SummaryTreatment for vitiligo is difficult and prolonged. Nevertheless, at present considerable knowledge accumulated during several decades on the pathogenic mechanisms, revealed important clues for designing new strategies to improve vitiligo depigmentation. With available medical therapies, high repigmentation percentages mostly on facial and neck lesions are achieved, although they are less effective on trunk and limbs and poor on the acral parts of the extremities. Narrow band UVB and psoralens and UVA ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 258 publications
(244 reference statements)
1
123
0
9
Order By: Relevance
“…Large grafts (>2 mm) have high risks on side effects like cobblestone formation (3,4,7,9). Hence, the current technique involves 1-to 1.5-mm superficial punch grafts, depending on anatomical location (10). Superficial punch grafts are the method of choice, since it is suggested that in thinner grafts, the superficial capillary network allows an earlier process of vascularisation, preventing side effects and the loss of grafts (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Large grafts (>2 mm) have high risks on side effects like cobblestone formation (3,4,7,9). Hence, the current technique involves 1-to 1.5-mm superficial punch grafts, depending on anatomical location (10). Superficial punch grafts are the method of choice, since it is suggested that in thinner grafts, the superficial capillary network allows an earlier process of vascularisation, preventing side effects and the loss of grafts (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The follicular repigmentation of the interfollicular epidermis in depigmented disorders, such as vitiligo, is supported by the observation that anatomic locations devoid of follicular units, Editorial such as glabrous skin, are significantly less responsive to phototherapy [23]. The areas that respond most favorably are the face and trunk, which contain numerous follicles [24].…”
Section: "The Presence Of Melanocytes In Grafts Is Crucial For Repigmmentioning
confidence: 80%
“…However, surgical methods can be used in refractory vitiligo, piebaldism or to obtain repigmentation in cases of thermal burns and trauma. The presence of melanocytes in grafts is crucial for repigmentation induced by surgical methods, which is most effective in completely depigmented skin versus hypopigmented lesions [23,25]. Patients can require several sessions for optimal recovery, which may result in decreased patient compliance.…”
Section: "The Presence Of Melanocytes In Grafts Is Crucial For Repigmmentioning
confidence: 99%
“…Tedavi çeşitleri, topikal steroidler, kalsinörin inhibitörleri, D vitamini analogları, fototerapi, lazer terapisi, cerrahi yöntemler olarak sayılabilmekte-dir. 7,25,26 Vitiligo tedavisinde yeni gelişmeler özetlene-cek olursa; vitiligoyu stabil hâle getirmek ya da repigmentasyon amaçlı uygulanan tedavilere devam etmektedir. Bununla birlikte, sadece monobenzon ile olan tedavi Amerikan Gıda ve İlaç Dairesi tarafından onay almış bulunmaktadır.…”
Section: Vi̇ti̇li̇go Tedavi̇si̇nde Seçenekler Ve Yeni̇ Geli̇şmelerunclassified